2011
DOI: 10.1158/1535-7163.mct-11-0243
|View full text |Cite
|
Sign up to set email alerts
|

Combining Curcumin (Diferuloylmethane) and Heat Shock Protein Inhibition for Neurofibromatosis 2 Treatment: Analysis of Response and Resistance Pathways

Abstract: Neurofibromatosis type 2 (NF2) is a genetic condition characterized by inactivation of the NF2 tumor suppressor gene and the development of schwannomas. The NF2 gene product, merlin, is activated (dephosphorylated) by contact inhibition and promotes growth suppression. We investigated the effect of curcumin (diferuloylmethane), a molecule with anti-inflammatory and antitumorigenic properties, on human schwannoma cell growth and the regulation of merlin by curcumin in both NF2 cells and neuroblastoma (non-NF2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…However, a recent study reported the coimmunoprecipitation of merlin with HSP70, which forms a multichaperone complex with HSP90 (21), implying that merlin may be regulated by or involved in the function of this complex. Identification of potential specificity of HSP90 inhibition in the NF2-deficient tumors will be the next step of the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent study reported the coimmunoprecipitation of merlin with HSP70, which forms a multichaperone complex with HSP90 (21), implying that merlin may be regulated by or involved in the function of this complex. Identification of potential specificity of HSP90 inhibition in the NF2-deficient tumors will be the next step of the study.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that the HSP90 complexes in tumor cells possess greater affinity to an HSP90 inhibitor 17-AAG, thereby promising selectivity for targeting tumor cells over normal cells (20). There is single report suggesting the efficacy of HSP90 inhibition in NF2 (21). Many known client proteins of HSP90 were found to be coactivated in human NF2-related tumors, such as ERBBs, AKT, and MET (refs.…”
Section: Introductionmentioning
confidence: 99%
“…MM cells express highly active NF-κB, and bortezomib inhibits tumor growth mainly by blocking the NF-κB signaling pathway [10]. This study showed that low concentrations of bortezomib did not affect NF-κB expression levels significantly, explaining the absence of both induced apoptosis and inhibition of proliferation.…”
Section: Discussionmentioning
confidence: 64%
“…Caffeic acid phenethyl ester (CAPE)-based extracts and artepillin C-based propolis from bee wax have been shown to suppress the growth of an NF1 -deficient malignant peripheral nerve sheath tumor cell line and a human papillomavirus E6/7 oncogene-immortalized vestibular schwannoma cell line, HEI-193 1819 ; however, the mechanisms by which CAPE and artepillin C suppress tumor growth are not understood. Curcumin found in turmeric, a spice derived from the rhizomes of Curcuma longa of the ginger family, was found to inhibit the growth of HEI-193 cells by down-regulating the phosphorylation of AKT and ERK1/2 20 . Honokiol, a lignan found in Magnolia grandiflora was also shown to exhibit antiproliferative activity in HEI-193 and inhibit ERK phosphorylation 21 .…”
Section: Discussionmentioning
confidence: 99%